Moderators of cognitive insight outcome in metacognitive training for first-episode psychosis. (September 2021) - González-Blanch, César; Birulés, Irene; Pousa, Esther; Barrigon, María Luisa; López-Carrilero, Raquel; Lorente-Rovira, Esther; Ayesa-Arriola, Rosa; Setien-Suero, Esther; Barajas, Ana; Grasa, Eva M.; Ruiz-Delgado, Isabel; González-Higueras, Fermín; et al.
Abstract: Metacognitive training (MCT) is a promising treatment for improving cognitive insight associated with delusional beliefs in individuals with psychotic disorders. The aim of this study was to examine potential moderators of cognitive insight in individuals with first-episode psychosis (FEP) who received either MCT or psychoeducation. The present study was based on data from a randomized control trial comparing MCT to psychoeducation. Baseline sociodemographic and clinical characteristics in a sample of 122 patients with FEP were examined as potential moderators of the self-reflectiveness and self-certainty dimensions of cognitive insight using the SPSS PROCESS macro. The only variable that moderated self-reflectiveness at the post-treatment evaluation was age of onset (b = −0.27, p = .025). The effect of MCT in reducing self-certainty was stronger in women (b = −3.26, p = .018) and in individuals with average or above average baseline self-esteem (b = −0.30, p = .007). Overall, our findings support the generalization of MCT to a variety of sociodemographic and clinical profiles. While some patient profiles may require targeted interventions such as MCT to improve cognitive insight, others may do equally as well with less demanding interventions such as a psychoeducational group.